Transparency and Budget Management in Spanish Municipalities - Gutiérrez Ponce, Herenia; Chamizo González, Julián; Cano Montero, Elisa Isabel (Revista del CLAD Reforma y Democracia, 2018)
AbstractThis article aimsto study the economic management of Spanish municipalities through theinformation of their budgets. The relevant expenditures items related totransparency and funding were identified in quest of sustainable andtransparent quantitative indicators. The budget management of several publicservices is analyzed to disclose transparency. The analysis is based onpublished databases of the Ministry of Public Finance. As a conclusiontransparency and tax-rate can be explained through specific items in theexpenditure budget, providing a sound basis for stakeholder to makeefficiency-based expenditure decisions using transparent indicators.
Keywords: Municipal Finances; Transparency; Efficiency; Local Administration; Budget; Economics Indicators; Spain